Cross-cultural adaptation and validation of the Spanish sensory processing sensitivity questionnaire (S-SPSQ) - Salinas-Quintana, Pedro J.; Barría-Ramírez, Rodolfo; Acevedo, Bianca P.; Vega-Muñoz, Alejandro; Pérez-Chacón, Manuela; Chacón, Antonio (Frontiers in Psychology, 2024)
Sensory Processing Sensitivity (SPS) is a biologically-based temperament trait characterized by heightened awareness, emotional responsivity, and reactivity to environmental stimuli. To facilitate measurement of SPS in Spanish-speaking populations, in this study we translated, adapted, and validated the Sensory Processing Sensitivity Questionnaire (SPSQ)-which provides a balanced measure of SPS including both positive and negative items-for Spanish-speaking persons. Employing a nonprobabilistic sampling method, we selected 1004 participants from diverse Spanish-speaking regions including XX. Confirmatory factor analysis, utilizing the diagonally weighted least squares method, was applied to validate the internal structure of the Spanish version of the SPSQ (S-SPSQ). Fit indices such as GFI, CFI, TLI, RMSEA, and SRMR were scrutinized. Reliability assessment utilized Cronbach's alpha and McDonald's Omega. Three models were examined: Model I (six factors) displayed robustness, Model II (six factors plus a general factor) did not show substantive improvement, and Model III (Higher Order and Bifactor) excelled in fit while balancing complexity and representation, thus validating the findings of the original SPSQ (De Gucht et al, 2022). When compared to the original SPSQ, the results of the S-SPSQ indicated similar reliability coefficients. Methodologically, this study contributes to cross-cultural questionnaire validations, prioritizing cultural sensitivity and facilitating the measurement of SPS in Spanish-speaking samples.